Safety evaluation after LASIK surgery based on the linear creep property: a finite element analysis - Ji-Xi Guo; Xue-Feng Li; Xin-Chao Wang; Xin-Heng Zhao; Yan Wang; Li-Hua Fang (International Journal of Ophthalmology)
AIM: To investigate the effect of the percent tissue altered (PTA) on the safety after laser-assisted in situ keratomileusis (LASIK) based on linear creep characteristics. METHODS: The linear creep characteristics of the cornea were characterized by the generalized Kelvin-Voigt constitutive relationship with five parameters. Then, the displacement and stress distribution on the anterior and posterior surfaces of the cornea were analyzed by constructing the eye model with different PTA. RESULTS: When PTA was above 39%, the vertex displacements under physiological intraocular pressure (IOP, 15 mm Hg) exceeded that of the preoperative glaucoma under average IOP. That is, an excessively high displacement value was found. In addition, with the increase of PTA, the central cornea was stretched thinner and more obviously due to IOP. When PTA was above 39%, the stress at the center of the anterior surface of the residual stroma was more than 20% larger than that of the normal human eye. The residual stroma was forced to stretch more severely due to excessive stress on the anterior surface. This resulted in deformation of the stroma and induced corneal ectasia. Meanwhile, the postoperative vertex displacement increased with the decrease in viscosity ratio. CONCLUSION: PTA less than 39% is the safe range for LASIK surgery. This study may provide a reliable numerical basis for postoperative corneal dilatation and the outcomes after refractive surgery.